PENGARUH PENGAMPUNAN PAJAK (TAX AMNESTY) DAN KESADARAN WAJIB PAJAK TERHADAP KEPATUHAN WAJIB PAJAK PADA KANTOR PELAYANAN PAJAK CIKARANG SELATAN - Asriani Natong (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2022)
The target for compliance with the Annual Tax Return (SPT) reporting which is expected by the Directorate General of Taxes (DGT) of the Ministry of Finance (Kemenkee) in 2019 is 85%. Taxpayer compliance in the South Cikarang KPP environment fluctuated during the 2015-2019 period. One of the factors decreasing taxpayer compliance is the lack of awareness of the taxpayers themselves. Another policy from the government is to issue a tax amnesty policy. The purpose of this study was to determine the tax amnesty, taxpayer awareness and taxpayer compliance contained in KPP Pratama Cikarang Selatan, to determine the effect of tax amnesty on taxpayer compliance at KPP Pratama Cikarang Selatan, to determine the effect of tax amnesty on taxpayer compliance. awareness of taxpayers on taxpayer compliance at KPP Pratama Cikarang Selatan, and the effect of tax amnesty and awareness of taxpayers together on taxpayer compliance at KPP Pratama Cikarang Selatan. The design of this research is a quantitative analysis method. The data analysis method in this research is descriptive analysis method and associative analysis method. The research population is taxpayers, both individuals and entities who are in the South Cikarang Pratama Tax Service Office. Determination of the sample using a quota sampling method with incidental sampling technique. The sample in this study were 50 people. Data collection techniques with questionnaires. Testing the instrument using the classical assumption test with the help of SPSS software version 23. The data analysis techniques used in this study were simple regression analysis and multiple regression analysis. The results showed that Tax Amnesty, Taxpayer Awareness and Taxpayer Compliance at KPP Pratama South Cikarang were quite good. There is an influence between Tax Amnesty (Tax Amnesty) on taxpayer compliance at KPP Pratama South Cikarang because the value of tcount > ttable (6,176 > 2,009). There is an influence between Taxpayer Awareness on Taxpayer Compliance at KPP Pratam Cikarang Selatan because the value of tcount > ttable (9.656 > 2.009). There is an influence between Tax Amnesty and Taxpayer Awareness on Taxpayer Compliance at KPP Pratama Cikarang Selatan because the value of tcount > ttable (48.672 > 3.20).